The end of the world in Egyptian funerary and magic texts and the destruction of Humanity in Heracleopolis Magna - Díaz-Iglesias Llanos, Lucía (ARYS. Antigüedad: Religiones y Sociedades, 2019)
In this article I bring forward a review of the allusions related to the end of the world inserted in funerary and magic texts belonging to different periods. I analyze the content, context and the implications of these mythological references. Then I explore the characterization of Heracleopolis Magna as a place where the uprising of gods and humans against the creator god and their subsequent annihilation occurred. Building on ideas of M. Smith and M. Kemboly about the solar mythical cycle and applied by these scholars to other compositions centered on the rebellion against the divine authority, I suggest a new interpretation for the mythical Heracleopolitan arguments of destruction: their counterpoint can be found in the perpetuation of the rule of the Sun god, who defeats his enemies and assumes sovereignty in Heracleopolis Magna.